The 2016-2063 Sexual and Reproductive Health and Reproductive Rights Neo-Colonizing Plan for Africa - Peeters, Marguerite (Chrześcijaństwo-Świat-Polityka, 2019)
The article presents the arguments demonstrating that Africa is subjected to the politics aimed at changing the perception of the issues concerning sexual ethics. In the name of improving security, sustainable development or freedom, some legal solutions are proposed, aimed at supporting abortion, using contraceptives, in vitro fertilization, sterilization or sexual education. One might think that developed countries are trying to impose on poor countries population politics which contradicts the principles of ethics and human rights.